2011
DOI: 10.5402/2011/467258
|View full text |Cite
|
Sign up to set email alerts
|

LigaSure Haemorrhoidectomy versus Conventional Diathermy for IV-Degree Haemorrhoids: Is It the Treatment of Choice? A Randomized, Clinical Trial

Abstract: Introduction. Milligan-Morgan haemorrhoidectomy performed with LigaSure system (LS) seems to be mainly effective where a large tissue demolition is required. This randomized study is designed to compare LigaSure haemorrohidectomy with conventional diathermy (CD) for treatment of IV-degree haemorrhoids. Methods. 52 patients with IV-degree haemorrhoids were randomized to two groups (conventional diathermy versus LigaSure haemorrhoidectomy). They were evaluated on the basis of the following main outcomes: mean op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 21 publications
2
28
0
6
Order By: Relevance
“…These findings are in consistent with the studies of Filingeri et al and Wang et al 12,13 Our findings reveals that there was no difference in the time required for the first bowel movement and in hospital stay between two groups which is in accordance with Gentile et al, study which concluded that there was no difference in hospital stay since patients were discharged 24±2 hours after the operation in both groups, and delayed discharges were registered in two cases of each group (III postoperative day) due to minor bleeding (2 conventional vs 1 vessel seal hemorrhoidectomy) and acute urinary retention (1 vessel seal hemorrhoidectomy) (P = 1 NS). 9 In our experience only one case of anal stenosis was detected and the incidence seems to be in line with the data of the literature (4-5%). This complication was treated by nifedipine topical ointment with a good final result, however as a useful trick to avoid the development of a circular scar, we preserved intact anoderm and mucosal bridges between the wounds.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in consistent with the studies of Filingeri et al and Wang et al 12,13 Our findings reveals that there was no difference in the time required for the first bowel movement and in hospital stay between two groups which is in accordance with Gentile et al, study which concluded that there was no difference in hospital stay since patients were discharged 24±2 hours after the operation in both groups, and delayed discharges were registered in two cases of each group (III postoperative day) due to minor bleeding (2 conventional vs 1 vessel seal hemorrhoidectomy) and acute urinary retention (1 vessel seal hemorrhoidectomy) (P = 1 NS). 9 In our experience only one case of anal stenosis was detected and the incidence seems to be in line with the data of the literature (4-5%). This complication was treated by nifedipine topical ointment with a good final result, however as a useful trick to avoid the development of a circular scar, we preserved intact anoderm and mucosal bridges between the wounds.…”
Section: Discussionsupporting
confidence: 91%
“…Compared with conventional hemorrhoidectomy, vessel sealing technique reduces mean operative time and requirement of analgesia as similar to the earlier studies. [9][10][11] Other studies have also emphasized that lower intraoperative bleeding. 10,11 Comparing early complication rates, nine cases in conventional hemorrhoidectomy method (5 bleeding and 4 acute urinary retention) and five cases in the vessel sealing group (2 bleeding, 2 urinary retention and 1 perianal abscess) These patients were managed conservatively and there was no need for redo surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in our study with LigaSure, an easily applicable and trainable method, the operation time was significantly shorter than in the conventional method (15 versus 20 min). In a study by Khanna et al (7), the hospitalization period after operation (1.4 versus 3.2 days) was significantly shorter in the LigaSure group; however, in a study by Gentile et al (13), the hospitalization periods of 24±2 h were similar in the two groups. In our study, the median hospitalization period was one day in both groups.…”
Section: Discussionmentioning
confidence: 88%
“…Development of anal stenosis due to thermal damage from LigaSure usage has been described in many recent studies. Filingeri et al (17) reported anal stenosis in 4 of 203 LigaSure-treated patients, Wang (18) determined it in 1 of 42 cases, and Gentile et al (13) reported it in 1 of 25 patients. In our study, the results for anal stenosis were similar to the literature (2.7%) (9,11).…”
Section: Discussionmentioning
confidence: 99%
“…Radiofrequency scalpel technique resulted in significantly less immediate postoperative pain after hemoroidectomy with respect to conventional diathermy techniques [9]. Two other randomized trials confirmed this finding [10,11]. Radiofrequency scalpel was associated with less postoperative pain when compared with harmonic scalpel in one randomized controlled trial [12].…”
Section: Complicationsmentioning
confidence: 94%